Two duodenal gastrointestinal stroma tumors: Management by minimally invasive surgery and then by conservative surgery. Issue 4 (26th December 2019) - Dembinski, Jeanne; Sabbagh, Charles; Chivot, Cyril; Le Mouel, Jean‐Philippe; Regimbeau, Jean‐Marc
Abstract: We report the case of a 48‐year‐old woman treated for a gastrointestinal stroma tumor of the duodenum after presenting with upper gastrointestinal bleeding. She was treated with a combination of a radiological and endoscopic approach and minimally invasive surgery. During follow‐up, the patient developed a second metachronous duodenal gastrointestinal stroma tumor, distinct from a local recurrence. This tumor was treated with a conservative surgical approach.